(untitled) (Biological Sciences - PJSIR, 2023)
Heavy metals are non-essential harmful substances that are transferred from environment to human body via food chain. The present study, therefore, investigated the uptake concentration of heavy metals including Cd, Cr, Cu, Fe and Mn by spinach, lettuce and coriander irrigated with Steel Mill and Khwar (stream) effluents. The concentration of heavy metals was within the safe limits in Tap water but it was high in Khwar effluent followed by Steel Mill effluents. The results indicated that Cd and Cu contents were within permissible limit in the tested vegetables.The concentration of Cr, Fe and Mn in the three vegetables irrigated with Steel Mill and Khwar effluents were above the FAO/WHO permissible limits. The order of concentration of heavy metals in vegetables and effluents was Khwar effluent > Steel Mill effluent > Tap water. The accrual order of heavy metals was spinach > lettuce > coriander. The relative order of heavy metals concentration in 3 vegetables irrigated with Khwar effluents was Mn> Fe > Cr > Cu > Cd. It was concluded that neither the untreated industrial waste water be used for irrigating crops nor vegetables and crops raised on such polluted water be consumed by humans and their domestic animals.